Aesthetic surgery fellowship at akademikliniken Stockholm: survey among graduates - Montemurro, Paolo; Diehm, Yannick; Hedén, Per; Fischer, Sebastian; Wagner, Johannes Maximilian (Aesthetic plastic surgery, 2025)
Aesthetic Surgery is one of the most competitive fields of plastic surgery. Although there is a certain demand for highly educated surgeons in this field, training in cosmetic procedures remains challenging. Akademikliniken Stockholm offers a highly appreciated fellowship program for aesthetic plastic surgeons and trained more than 200 surgeons from all over the world.